Cutaneous Larva Migrans Pada Anak Usia 3 Tahun - Maya Nurul Hidayati (Medula, 2020)
Cutaneous larva migrans (CLM) or creeping eruption is a skin disease that makes inflammation of the skin in a linear or meandering form caused by invasion of hookworm larvae. CLM can be found in tropical and subtropical regions of the world, especially in warm, humid and sandy regions. An estimated 576-740 million people in the world are infected with hookworm. In Indonesia the prevalence of hookworm infection is around 30-50% where in plantation areas it has a higher prevalence. This case report describes a child 3 years old with complaints a reddish rash meandering on the right lower leg that felt itchy. On physical examination dermatologic alobtained at dextra cruris region are erythematous papules, multiple, linear, serpiginosa are partially covered in crust. Patients was diagnosed with Cutaneous larva migrans and given antihelmin medication and education.